2016
DOI: 10.1016/j.trgeo.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical modelling of ballasted railway track foundations for high-speed trains with special reference to critical speed

Abstract: Due to recent congestion of highways in many countries around the world, railways have become the most popular means of public transportation, which has increased the demand for heavier and faster trains. High speeds and heavy loads of trains are usually accompanied with large vibrations in the train-track-ground system, especially when train speed reaches its critical value, leading to possible train derailment and track damages. This unwanted scenario makes it important for railway geotechnical engineers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 22 publications
1
48
0
2
Order By: Relevance
“…The results show that the subgrade nonlinear model resulted in slightly higher vertical deflections than those obtained from both the linear and elastoplastic models. As found by Sayeed and Shahin [15], the consideration of linear elastic and nonlinear elastic behaviour of geomaterials do not yield a significant variation in terms of the vertical sleeper deflections, particularly in case of stiff subgrade. So, it can be Similarly, Figures 9 and 10 compare the time history of vertical stress (σz) and deviatoric stress (q) obtained using different subgrade constitutive models at Points E to H designated in Figure 4.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…The results show that the subgrade nonlinear model resulted in slightly higher vertical deflections than those obtained from both the linear and elastoplastic models. As found by Sayeed and Shahin [15], the consideration of linear elastic and nonlinear elastic behaviour of geomaterials do not yield a significant variation in terms of the vertical sleeper deflections, particularly in case of stiff subgrade. So, it can be Similarly, Figures 9 and 10 compare the time history of vertical stress (σz) and deviatoric stress (q) obtained using different subgrade constitutive models at Points E to H designated in Figure 4.…”
Section: Methodsmentioning
confidence: 54%
“…In this paper, the dynamic response of track-ground system subjected to train moving loads was investigated for some design aspects of ballasted railway track foundations, including the validity of the simpler linear elastic behaviour of track geo-materials compared to the more realistic nonlinear elastic and elastoplastic simulations. The current study is carried out using an advanced three-dimensional (3D) finite element (FE) numerical model that was previously developed by the authors [14,15] and validated against field measurements data.…”
Section: Introductionmentioning
confidence: 99%
“…Alves Costa et al 2015;Sayeed and Shahin 2016a) indicated that the DAF is significantly influenced by the subgrade characteristics. Moreover, due to resonance, catastrophic track deflection may occur when the train speed approaches the critical speed (Krylov 1994;Madshus and Kaynia 1999;Yang et al 2009), which is also significantly influenced by the modulus and thickness of the subgrade medium and train geometry (Alves Costa et al 2015;Sayeed and Shahin 2016b). Unfortunately, there are currently no proper guidelines for considering the critical speed in any available design method.…”
Section: Development Of New Design Methodsmentioning
confidence: 99%
“…The 3D FE numerical model developed in this paper was previously established by the authors (Sayeed and Shahin 2015;Sayeed and Shahin 2016b) and validated against data of field measurements obtained from Cunha and Correia (2012) and Kaynia et al (2000). The 3D FE numerical model is used herein to investigate the dynamic response of the train-trackground system subjected to train moving loads, for the deviatoric stress analyses, which is shown in Fig Table 3, and the range of variables considered are given in Table 4.…”
Section: Deviatoric Stress Characteristics Of Track Substructurementioning
confidence: 99%
“…This issue affects all types of tracks including conventional ballasted track [8], [9], ballastless tracks [10], [11], asphalted track [12] and even more modern rail transportation mode, maglevs [13]. The vibration analysis methods can be divided into three categories: (a) experimental methods; (b) analytical; and (c) numerical methods.…”
Section: Introductionmentioning
confidence: 99%